Julián Calvo Blanco: A freemason jurist from Spain exiled in Mexico - Martínez Chávez, Eva Elizabeth (2019)
This paper analyzes the life and work of Julián Calvo Blanco, a Spanish jurist exiled in Mexico after the Spanish Civil War, in order to study the relationship between Freemasonry and the Spanish exiles. Our research was based primarily on historical archives in Mexico and Spain thus gathering information on his life in Spain before exile, the voyage that brought him to Mexico, and his participation in Freemasonry in both countries. The details of his activities as a Mason increase our knowledge of Mexican Freemasonry’s part in the arrival and incorporation of quite a few Spanish Masons.